Impact of paediatric tonsillectomy perioperative management on pain, nausea and recovery: A prospective cohort study. (29th May 2019) - Richards, Julianne; Lang, Mary; Andresen, Elizabeth; O'Leary, Kathryn; Jauncey‐Cooke, Jacqueline; Anderson, Nicole; Burns, Hannah; Slee, Nicola; Ullman, Amanda J; Cooke, Marie
Abstract : Aim: Tonsillectomy procedures are a core element of paediatrics; however, perioperative management differs. This study aimed to describe tonsillectomy management, including the burden of pain, nausea and delayed recovery. Methods: A prospective cohort study was undertaken through an audit of tonsillectomy perioperative practice and recovery and survey interviews with family members 7–14 days post‐surgery. The study was undertaken at an Australian tertiary referral paediatric hospital between June and September 2016. Results: The audit included 255 children undergoing tonsillectomy, with 127 family members interviewed. Most participants underwent adenotonsillectomy ( n = 216; 85%), with a primary diagnosis of obstructive sleep apnoea ( n = 205; 80%) and a mean age of 7 years (standard deviation; 3.9). A variety of intra‐operative pain relief and antiemetics was administered. Pain was present in 29% ( n = 26) of participants at ward return, increasing to 32–45% at 4–20 h and decreasing to 21% ( n = 15) at discharge. A third of the children (32%; n = 41) had moderate to severe pain at post‐discharge interview, and 30% ( n = 38) experienced nausea at home. Most parents (82%; n = 104) were still giving regular paracetamol at 7 days post‐operatively, and 31% ( n = 39) had finished their oxycodone. Of the participants, 14% ( n = 26) presented to the emergency department within 7 days of discharge; 8% ( n = 20) of the total cohort were re‐admitted. Conclusions: There was variety in perioperative and post‐discharge care. Pain scores were infrequently documented post‐tonsillectomy, and parents are generally dissatisfied with the management of post‐operative pain and nausea. Further research is needed to provide a more consistent approach to perioperative management to promote recovery.